Assessment of performance of clarias gariepinus (african catfish) juveniles on diets supplemented with kola pod husk (cola nitida) (2012)
A twelve -week feeding trial was carried out to assess the nutritive potentials of kola pod husk and to assess the growth performance of Clarias gariepinus juveniles on varying levels of kola pod husk- supplementation. The objective of this study was to assess the nutritive potentials of kola pod husk on the performance of C. gariepinus and its level of incorporation in such diets. Eight experimental bowls (60x3Ox30cm3) were used for the experiment. There were four treatments with each treatment having two replicates. The fish had initial mean body weight of 10.56g. The experimental diets were formulated at 38% crude protein and the fish fed at 5% of their body weight three times per day with graded levels of 0, 10,20, and 30% of ko la pod husk. 15 fish were stocked per replicate. Proximate composition of fish before and after the experiment, proximate composition of kola pod husk, the growth performance and nutrient utilization of feed by fish were determined. Significant differences were observed between the control diet and 10 -20 % inclusion of kola nut pod husk with the control having the best growth indices. However fish on 30 % kola pod husk inclusion performed best among kola nut pod husk -containing diets .There was no significant difference between 30 % inclusion of kolanut pod husk and the control diet on all parameters considered. The inclusion of 30% sun -dried and kola nut pod husk produced the best growth performance of the experimental fish and could be considered as a potential energy supplier in C. gariepinus juveniles" diets subject to further studies